Research Advances in the Role of the Poly ADP Ribose Polymerase Family in Cancer - Sha, Huanhuan; Gan, Yujie; Zou, Renrui; Wu, Jianzhong; Feng, Jifeng (Frontiers in Oncology, 2021)
Poly ADP ribose polymerases (PARPs) catalyze the modification of acceptor proteins, DNA, or RNA with ADP-ribose, which plays an important role in maintaining genomic stability and regulating signaling pathways. The rapid development of PARP1/2 inhibitors for the treatment of ovarian and breast cancers has advanced research on other PARP family members for the treatment of cancer. This paper reviews the role of PARP family members (except PARP1/2 and tankyrases) in cancer and the underlying regulatory mechanisms, which will establish a molecular basis for the clinical application of PARPs in the future.